2022
DOI: 10.3390/foods12010011
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cherry Seed Oil Using Conventional Techniques and Supercritical Fluid Extraction

Abstract: This study aims to compare the suitability of three extraction techniques (cold pressing, Soxhlet and supercritical fluid extraction (SFE)) to isolate oil from cherry seeds. Oils were examined in terms of extraction yield, fatty acids profile, tocopherols yield and antioxidant activity. Additionally, influence of SFE parameters was evaluated using one-factor-at-a-time design with pressure (200–350 bar), temperature (40–70 °C), flow rate (0.2–0.4 kg/h) and particle size (<800 µm and >800 µm). Oil yields r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, Ianni et al [ 28 ] suggested that improved antioxidant activity could come as the result of a synergism between multiple compounds, other than the phenols in the mixture, capable of reacting in the free-radical-scavenging mechanism. It was already confirmed that the lipophilic fraction of cherry seeds could express significant radical-scavenging capacity towards DPPH and ABTS + radicals [ 29 ]. Therefore, it is suggested that lipophilics, such as tocopherols, might contribute to the improvement of the antioxidant action of cherry seed extracts obtained by NADES extraction.…”
Section: Resultsmentioning
confidence: 97%
“…However, Ianni et al [ 28 ] suggested that improved antioxidant activity could come as the result of a synergism between multiple compounds, other than the phenols in the mixture, capable of reacting in the free-radical-scavenging mechanism. It was already confirmed that the lipophilic fraction of cherry seeds could express significant radical-scavenging capacity towards DPPH and ABTS + radicals [ 29 ]. Therefore, it is suggested that lipophilics, such as tocopherols, might contribute to the improvement of the antioxidant action of cherry seed extracts obtained by NADES extraction.…”
Section: Resultsmentioning
confidence: 97%
“…As can be seen, the levels of total tocols varied over a wide range, from 3.4 mg/100 g for commercial cold-pressed parsley oil produced in the USA [159] to 581.3 mg/100 g in oil from radish seeds originated from China obtained with the use of super-critical carbon dioxide extraction [213]. The noticeably low contents (<20 mg/100 g) of these compounds were also determined in some oils from the apple [58,145], apricot [132], blueberry [59,160], cherry [77], raspberry [112], strawberry [72,130,140], broccoli [131], and carrot seeds [131]. However, some researchers reported that the content of total tocols in oils from apple and raspberry seeds can reach up to 379.1 and 315.2 mg/100 g, respectively [90,128].…”
Section: Variation In the Tocols Content Of Oils From Unconventional ...mentioning
confidence: 99%
“…The objective of the conducted study by Dimic et al [131] was to assess the efficacy of Soxhlet extraction to isolate oil from cherry seeds. The investigation focused on the analysis of oils with regard to their extraction yield, fatty acid composition, TTC, and antioxidant capacity.…”
Section: Combination Of Conventional and Green Extraction Techniques ...mentioning
confidence: 99%
“…Oleic acid (25-41%), linoleic acid (39.1-46.2%), α-linolenic acid (0.09-0.43%), α-eleostearic acid (~8-15%), total sterol content (495 mg/100 g oil), total tocochromanol content (134 mg/100 g oil), TPC (22.8 µg GAE/g), total carotenoid content (0.84 mg/100 g oil) [69] 1:4 solid-to-liquid ratio with n-hexane or methylene chloride for 6 h Oleic acid (41.44-41.46 g/100 g seed oil), linoleic acid (47.00-47.17 g/100 g seed oil), α-linolenic acid (0.32-0.33 g/100 g seed oil), TTC (37.37-46.36 mg/100 g seed oil) [131] "Green" SC-CO 2 Extraction at 60…”
Section: Combination Of Conventional and Green Extraction Techniques ...mentioning
confidence: 99%